Peningkatan Pengetahuan, Sikap, dan Tindakan Cuci Tangan Enam Langkah WHO Siswa SD Negeri 1 Iroyudan: Studi One Group Pretest-Posttest - Teguh Ariyanto; Arief Budiarto; Aninstya, Mayang Rachma (Direktorat Pengabdian kepada Masyarakat, 2023)
One effort to reduce infectious diseases by the National Medium-Term Development Plan in the health sector for the 2020-2024 period is through the Handwashing with Soap Program (HWWS). This program aimed to minimize disease transmitted through hands, especially among schoolchildren. Therefore, effective and proper promotion about HWWS is needed. This research aims to determine the differences before and after the intervention related to knowledge, attitudes, and skills of HWWS based on the WHO six-step handwashing guidelines. This study is a pre-experimental research with a one-group pretest-posttest study design conducted on students in grades 4, 5, and 6 at SDN 1 Iroyudan. The independent variable is health promotion through presentations, posters, and direct demonstrations, while the dependent variables are students' knowledge, attitudes, and skills related to HWWS. Univariate analysis was conducted to determine the frequency distribution and percentage of each variable. The normality of research data was determined by the Shapiro-Wilk test. Bivariate analysis was performed using the Paired T-test if the research data had a normal distribution. If the research data did not have a normal distribution, the Wilcoxon Signed Ranks Test was used. The research results are means with a 95% confidence interval. There were 39 students from grades 4, 5, and 6 at SDN 1 Iroyudan, consisting of 24 male students and 15 female students. The mean pretest knowledge score of students was 17.15, while after the intervention, it became 19.56 (p-value 0.000). The mean pretest attitude score of students was 17.10, while after the intervention, it became 19.49 (p-value 0.000). The mean pretest skill score of students was 5.85, while after the intervention, it became 11.85 (p-value 0.000). This indicates a statistically significant difference before and after the intervention in the mean values of knowledge, attitudes, and skills of students related to HWWS according to WHO.